Contextualising school readiness in South Africa: Stakeholders’ perspectives - Erica Munnik; Mario Smith (South African Journal of Childhood Education, 2019)
Background: Preparing children for mainstream school occurs in systems that act as an overarching context. The perspectives of stakeholders influence how they prepare children for mainstream education.